Decoding Facial Dissymmetry: A Comparative Morphological Study on Human Skulls and Facial Structures - Marc Divaris, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. This study provides a detailed examination of facial asymmetry and its relationship with skeletal structure and soft tissues, aiming to better understand the morphological variations of the face. Methods:. The facial characteristics of 615 patients were analyzed using morphometric measurements. To complement this analysis, 189 skulls were examined to establish a concordance between skeletal structure and soft tissues, allowing for a deeper understanding of the observed asymmetry. The data were statistically analyzed to identify patterns of asymmetry. Results:. The measurements revealed a prevalence of the “narrow face” on the right side, characterized by features such as a narrower orbit, a thinner lateronasal area, and a slightly higher and narrower maxillomalar block. Notable exceptions to this pattern were observed, indicating significant individual variations. Conclusions:. Facial asymmetry is a constant feature among individuals and is influenced by complex embryological development processes. Identifying these variations provides new insights for aesthetic procedures, emphasizing the importance of a personalized approach to facial diagnosis.